Integrating Multimedia Presentations to Enhance Linguistic and Digital Literacy in Higher Education - Mustakim, Mustakim; Rosmiana, Sri; Ismail, Ismail (Majesty Journal, 2024)
The digital era has transformed education, making linguistic and digital literacy essential skills for success. This study aimed to evaluate the impact of multimedia presentations on these literacies within the English Education Program at Universitas Muhammadiyah Enrekang. Using a mixed-methods approach, the research measured improvements in students' skills through pre-test and post-test assessments, multimedia artifact evaluations, reflective journal entries, and lecturer observations. The results revealed significant enhancements in both linguistic and digital literacy, with students demonstrating improved language use and technical proficiency. Thematic analysis of journal entries highlighted skill development and challenges, emphasizing the importance of a supportive learning environment. Lecturer observations confirmed high levels of engagement and collaboration. The study underscores the need for innovative pedagogical frameworks and professional development for educators to effectively integrate multimedia tools. These findings contribute to the existing knowledge by demonstrating the potential of multimedia presentations to enhance educational outcomes and prepare students for the demands of the modern world. Future research should explore the long-term effects of multimedia tools on literacy development and consider cultural factors in educational strategies.